Study of complexes of cadmium with some L-amino acids and vitamin-C by voltammetric technique - Khan, Farid; Khanam, Afroza (Eclética Química, 2008)
Voltammetric technique was used to study the binary and ternary complexes of cadmium with L-amino acids and vitamin-C (L-ascorbic acid) at pH =7.30 ± 0.01, μ = 1.0M KNO3 at 25ºC and 35ºC. Cd (II) formed 1:1:1, 1:1:2 and 1:2:1 complexes with L-lysine, L-ornithine, L-threonine, L-serine, L-phenylglycine, L-phenylalanine, L-glutamic acid and L-aspartic acid used as primary ligands and L-ascorbic acid used as secondary ligand. The trend of stability constant of complexes was Llysine < L-ornithine < L-threonine < L-serine < L-phenylglycine < L-phenylalanine < L-glutamic acid < L-aspartic acid which can be explained on the basis of size, basicity and steric hindrance of ligands. The values of stability constant (log β) varied from 2.23 to11.33 confirm that these drugs i.e. L-amino acids or in combination with L-ascorbic acid or their complexes could be used against Cd (II) toxicity. The study has been carried out at 35ºC also to determine the thermodynamic parameters such as enthalpy change (ΔH), Free energy change (ΔG) and entropy change (ΔS) respectively.